2018
DOI: 10.1021/acsnano.8b04947
|View full text |Cite
|
Sign up to set email alerts
|

Dense and Dynamic Polyethylene Glycol Shells Cloak Nanoparticles from Uptake by Liver Endothelial Cells for Long Blood Circulation

Abstract: Research into long-circulating nanoparticles has in the past focused on reducing their clearance by macrophages. By engineering a hierarchical polyethylene glycol (PEG) structure on nanoparticle surfaces, we revealed an alternative mechanism to enhance nanoparticle blood circulation. The conjugation of a second PEG layer at a density close to but lower than the mushroom-to-brush transition regime on conventional PEGylated nanoparticles dramatically prolongs their blood circulation via reduced nanoparticle upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(145 citation statements)
references
References 68 publications
8
134
0
Order By: Relevance
“…The use of longer and more densely packed dextran did not cause any relevant amount of complement activation through any pathway. These results somewhat consolidate what was previously established for PEG (Zhou et al, 2018).…”
Section: Synthetic Approachessupporting
confidence: 91%
“…The use of longer and more densely packed dextran did not cause any relevant amount of complement activation through any pathway. These results somewhat consolidate what was previously established for PEG (Zhou et al, 2018).…”
Section: Synthetic Approachessupporting
confidence: 91%
“…Click reaction between azide and alkyne was then performed to decorate the micelle with anti‐PD‐1 antibodies via matrix metalloproteinase‐2 (MMP‐2) sensitive peptide linker and sheddable long‐chain PEG (PEG 20k ) via acid‐labile bond. Owing the long circulation of stealth nanoparticles with PEG corona, the micelle named sAMcP may co‐deliver aPD‐1 and PTX into tumor site via passive tumor accumulation. Then, PEG 20k shedding and aPD‐1 release may be triggered by the weak acidity (pH ≈ 6.5) and enriched MMP‐2 (10–50 × 10 −9 m ) of tumor microenvironment, respectively, which may also turn the negatively charged micelle to a positively charged one (McP) for an easy internalization into cancer cells because of the detachment of negatively charged antibody and partial protonation of Dip groups.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the interaction of these nanoparticles with fetal bovine serum showed that all the PEGylated particles generated adsorbed a similar quantity of proteins, which was smaller than the amount of protein found in the non-PEGylated particles (as previously shown). However, particles with a double layer of PEG bound to proteins with different binding affinities [49]. .…”
Section: Pegylated Coatingsmentioning
confidence: 99%